Strengthening mutual accountability and performance in agriculture in Southern Africa - Nhemachena, Charles; Matchaya, Greenwell C.; Nhlengethwa, Sibusiso (Academy of Science of South Africa, 2018)
We critically assessed experiences in the implementation of agricultural joint sector reviews in supporting mutual accountability in Southern Africa, focusing on the lessons learned, the challenges and recommendations for improvement. Empirical data were gathered from four countries that have implemented joint sector reviews: Malawi, Mozambique, Swaziland and Zambia. The results show that recent efforts to conduct joint sector review assessments in these countries have raised the quest for increased accountability for action and results. Despite progress to strengthen mutual accountability in the countries, monitoring and evaluation capacity remains a concern, especially at sub-national levels. The mutual accountability process and implementation of the agricultural joint sector review processes in the respective countries have come a long way in facilitating sector-wide engagement of stakeholders in planning, implementation and monitoring and evaluation of agricultural policies and programmes. These processes are critical to ensure effective implementation and realisation of development impacts of agricultural priorities in the national agricultural investment plans.